On theorems of R. Rado and of D. Watson - V. L. Dol'nikov (Моделирование и анализ информационных систем)
Theorems of R. Rado and of D. Watson are generalizations for theorems P. Kirchberger and C. Caratheodory. In the paper we will consider some generalizations and refinements for these theorems .